Study of Brain-Type Natriuretic Peptide in Children with Epileptic Seizures - Bediar, Hamdi M.; Azouz, Hanan G.; El-Bordeni, Magdi M.; Elsakka, Elham E.; Nour El-Din, Mohamed A. (Journal of Pediatric Epilepsy, 2016)
Background Elevated N-terminal of the prohormone brain natriuretic peptide (NT-proBNP) concentrations in childhood epilepsy and febrile convulsions has been reported. The present study was conducted on 30 children at Alexandria University Children's Hospital. They have been classified into two groups: (1) seizures group which included 20 postictal children (10 males and 10 females), subdivided into 10 children with partial epilepsy who had partial motor seizures (PS) and 10 children with idiopathic generalized epilepsy who had tonic–clonic seizures and (2) control group which included 10 children (8 males and 2 females) who was randomly selected from epileptic children after a seizure-free period of at least for 2 months. All cases and controls were subjected to full history taking, clinical examination with emphasis on neurological examination, and routine laboratory investigations to exclude any disease that may alter serum level of BNP, such as cardiac, renal, or hepatic disease. For seizures group, plasma concentration (NT-proBNP) was measured within 4 hours after seizure onset and again 24 to 48 hours later. For control group NT-proBNP was measured once. Subanalyses were done and plasma NT-proBNP levels in each subgroup of postseizure group within 4 hours postictal were compared with NT-proBNP levels among control group.Results NT-proBNP plasma concentrations within 4 hours postictal were significantly higher among the postseizure group compared with the control group. Significant decrease of NT-proBNP levels in the postseizure group was observed after the 24- to 48-hour follow-up. NT-proBNP plasma concentrations were significantly higher among patients with generalized seizures compared with controls.Conclusion Plasma NT-proBNP assay when measured in the appropriate clinical setting may be useful in the diagnosis of childhood epilepsy.
Keywords: brain type natriuretic peptide; epilepsy; NT-proBNP; generalized seizures; partial seizures